Abstractions (Nature (London), 2009)
Decisions, decisions How do we change our minds? Theoretical neuroscientists have developed plausible models for how the brain comes to a decision based on 'noisy' and often ambiguous information, but these assume that once that decision is made, it is made for good. Now a series of experiments on subjects who were asked to move a handle to one of two positions dependent on a noisy visual stimulus has been used to develop a new model that accounts for how and when we change our mind after we make a decision. Analysis of the rare occasions where subjects changed their mind half way through selecting their answer shows that even after making a decision the brain continues to process the information it had gathered — information still in the processing pipeline— to either reverse or reaffirm its initial decision. The new theory introduces the acts of vacillation and self correction into the decision-making process.